OPTIMASI HYDRAULIC PUMPING UNIT PADA SUMUR “WN-98” LAPANGAN “X” - Nirwana Sima; Firdaus Firdaus; Jan Friadi Sinaga (PETROGAS: Journal of Energy and Technology, 2022)
The Hydraulic Pumping Unit installed in the WN-98 well experienced a decrease in production because the longer it was produced, the installed pump capacity was no longer in accordance with the formation production capacity. From the initial data, it is known that the production flow rate is 68 bpd, seen from the production capacity of the WN-98 well, the maximum flow rate of 83.46, there is still potential for the well to produce more. So, the pump optimization calculation is carried out to increase the production rate from the previous one. This optimization is carried out using two scenarios in scenario one, calculating pump optimization using a 2-inch plunger with 5/8 dan ½ inch rods. In screnario two, calculate the pump optimization using a plunger of the size 1 ¾ inch and rod 5/8 and ½ inch. The production clothes obtained in scenario 1 are 64 bpd, the pump stroke length is 52 inch and pump speed is 4.1 spm. In the results of scenario 2, the production rate is 77.8 bpd, the pump stroke length is 64 inch and the pump speed is 4.2 spm. Between the two scenarios, the best scenario is scenario 2 because the production rate increases from the initial production flow rate, from the initial production flow rate, from 68 bpd to 77.8 bpd.